A General Family of Fifth-Order Methods for Finding Simple Roots of Nonlinear Equations - GHANBARI, Behzad (Walailak Journal of Science and Technology (WJST), 2012)
In this paper, a new fifth-order family of methods free from second derivative is obtained. The new iterative family contains the King’s, which is one of the most well-known family of methods for solving nonlinear equations, and some other known methods as its particular case. To illustrate the efficiency and performance of proposed family, several numerical examples are presented. Numerical results illustrate better efficiency and performance of the presented methods in comparison with the other compared fifth-order methods. Therefore, the proposed family can be effectively used for solving nonlinear equations.